Keragaan dan Produksi Umbi G2 Kentang Menggunakan Sumber Benih yang Berbeda - Azhari, Andi; Maharijaya, Awang; Sobir (Jurnal Hortikultura Indonesia, 2019)
Potato (Solanum tuberosum L.) seed production by using tubers and cuttings from two local varieties have been conducted to determine their performance and production in the field. Currently in Indonesia, the use of potato cuttings is limited to the production of G0 and G1 tuber seeds in controlled conditions (greenhouse or screenhouse). This research used a factorial Randomized Complete Block Design with varieties (RGH01 and Medians) and seed sources (tubers (G0) and cuttings) as the factor and five replication. The data were analyzed using analysis of variance followed by Duncan's multiple range tests. The result showed that the plants derived from cuttings on both varieties produced more leaves and branches. Otherwise plant height were not significantly different. The production of tubers was not significantly different with 5.2 to 5.9 tubers per plant. Tuber yield of plants derived from tubers on both cultivars was higher than the plants derived from cuttings. However small size tuber (< 40 g) percentage of plants derived from cuttings was higher with 82.0% (Medians) and 94.1% (RGH01) per plant.Keywords: cuttings, potato propagation, seed propagation, Solanum tuberosum L., tuber